## coolaidd 2 years ago Find g(f(x)) for f(x) = -3x – 6 and G(x)=(-1/2)x+3

1. v4xN0s

Simplify this (-1/2)(-3x-6)+3

Multiply (-3x-6) and (-1/2x+3).

3. Kira_Yamato

Is $G(x) = \int\limits g(x) dx$

4. v4xN0s

radh thats not right and there is no need for integrals here...

5. v4xN0s

its just simple substitution

How is it not right? you multiply g(x) * f(x)..?

7. coolaidd

3/2x+6 ?

8. v4xN0s

you dont multiply you substitue f(x) into g(x)

9. coolaidd

im saying is this the answer?

Ah, I understand. Sorry.

11. v4xN0s

12. coolaidd

oh ok.. thanks!

13. coolaidd

What about : Find f(g(x)) for f(x) = -3x – 6 and g(x)=-1/2x+3

14. coolaidd

3/2x+6?

15. v4xN0s

Oh wow im so sorry i switched then up

16. v4xN0s

3/2x+6 is the right answer to the first one and 3/2x-15 is the answer to the second one

17. coolaidd

i see!

18. Kira_Yamato

I suppose the thing is for all Real values of x. gf(x) = (-1/2)(-3x – 6)+3 gf(x) = 3/2 x + 6

19. coolaidd

thanksss

20. Kira_Yamato

Sorry if I confuse you because I thought G'(x) = g(x) --> saw that in a textbook when I visit Singapore